Magnetic field tunable vortex diode made of YBa2Cu3O7−δ Josephson junction asymmetrical arrays - Chesca, Boris; John, Daniel; Pollett, Richard; Gaifullin, Marat; Cox, Jonathan; Mellor, Christopher; Savelev, Sergey (AIP Publishing, 2017)
Several Josephson ratchets designed as asymmetrically structured parallel-series arrays of Josephson junctions made of YBa2Cu3O7−δ have been fabricated. From the current-voltage characteristics measured for various values of applied magnetic field, B, in the temperature range of 10–89 K, we demonstrate that the devices work as magnetic field-tunable highly reversible vortex diodes. Thus, at 89 K, the ratchet efficiency η could be reversed from +60% to −60% with a change in B as small as 3 μT. By decreasing the operation temperature, η improves up to −95% at 10 K while the dynamics in the B-tunability degrades. The ratchet designs we propose here can be used to control unidirectional vortex flow vortices in superconducting devices as well as building integrated nano-magnetic sensors. Numerical simulations qualitatively confirm our experimental findings and also provide insight into the related and more general problem of the control of the transport of nano/quantum objects in thin films.